‘Des mémoires sur la vie de cet illustre philosophe’: George Leman Tuthill’s Unwritten Biography of Diderot - Caroline Warman (Modern Languages Open)
This essay analyses for the first time two letters written in 1805 by an Englishman, George Leman Tuthill (1772–1835), to Diderot’s literary executor Jacques-André Naigeon (1735–1810), stating his desire to write a biography of Diderot in English and asking to see the unpublished manuscript of Naigeon’s Mémoires sur Diderot. Naigeon never replied, but he kept the letters. They are now in an archive with Naigeon’s manuscript in the Bibliothèque Carnegie de Reims. Tuthill later trained as a doctor and became renowned as a physician to various asylums; he therefore boasts an entry in the Oxford Dictionary of National Biography, but nothing appears there about his earlier ambitions with respect to Diderot, and Diderot scholarship has known nothing about his existence. This piece brings together these two worlds, supplementing the portrait with further information from his correspondence with the famed Sinologist Thomas Manning (1772–1840) and from their mutual friend the writer Charles Lamb (1775–1834). Tuthill emerges as a figure involved in a Romantic circle, a man of many parts, not all of which fitted together seamlessly. His thwarted ambition to be Diderot’s first English biographer is evidence of greater interest in and awareness of Diderot in such circles than had previously been thought. The final section of the essay considers why Naigeon did not reply, and looks at the position of known atheists and Naigeon in particular at that time.